PENGARUH CITRA DAN PROSPEK PRODI TERHADAP KEPUTUSAN STUDI MAHASISWA PADA PROGRAM PENDIDIKAN PARIWISATA - Apit Buchori (Kepariwisataan: Jurnal Ilmiah, 2021)
This study was conducted to see how much influence the organizational image and study program prospects have on student decision making in choosing the Department of Tourism Studies at the Ambarrukmo Tourism College, Yogyakarta, both gradually and simultaneously. This research is a causal associative study with a quantitative approach. The variable of this study is image. organization, study program prospects and student purchasing decisions. The object of this research is the student population of the STIPRAM Tourism Study Program class 2018/2019 as many as 110 students, consisting of 70 women and 40 men.as a sample through proportional random sampling technique.Data collection method by conducting questionnaires and data analysis used is multiple linear regression. The results showed that:.(1) The image of the study program has a positive and relevant effect on student decisions as indicated by the value of tcount = 6.120 with a significance of 0.000. (2) Likewise, the prospect of study programs has a positive and quite large influence on student decisions as seen from the value of tcount = 3,479 with a significance of 0.001.Keywords: Organizational Image, Study Program Prospects, Decision Making